Environmentally friendly and facile synthesis of Rh nanoparticles at room temperature by alkaline ethanol solution and their application for ethanol electrooxidation. Issue 6 (13th January 2017) - Li, Fuhai; Weng, Hanqin; Shang, Yun; Ding, Zuoming; Yang, Zheng; Cheng, Sheng; Lin, Mingzhang
Abstract : A facile, fact and green synthetic route was developed to prepare Rh nanoparticles at room temperature. Abstract : Rhodium (Rh) is one of the most important catalyst constituents in many industrial catalytic processes. The synthesis of rhodium nanoparticles (RhNps) has received considerable interest for decades. In this paper, we report an environmentally friendly and facile synthesis route of RhNps through direct reduction of RhCl3 by ethanol in an alkaline medium in the presence of PVP at room temperature, confirmed by UV-vis spectroscopy, TEM, XRD and XPS. The effects of the concentrations of OH − and ethanol, as well as the nature of the alcohols, which greatly affected the formation rate of RhNps, were systematically investigated to understand the mechanism. Our results support that ethoxy anions generated from the deprotonation of ethanol were highly active and responsible for the formation of RhNps. Electrochemical tests have shown that Rh/C displayed zero activity in an acid medium, while in an alkaline medium Rh/C was highly active and displayed enhanced catalytic activity towards ethanol oxidation compared to commercial Rh/C. The process presented in this work is expected to be useful for preparing Rh-based nanocatalysts at room temperature, which may be extended to other nanocatalysts.